2012
DOI: 10.3389/fnins.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

What are the Odds? The Neural Correlates of Active Choice during Gambling

Abstract: Gambling is a widespread recreational activity and requires pitting the values of potential wins and losses against their probability of occurrence. Neuropsychological research showed that betting behavior on laboratory gambling tasks is highly sensitive to focal lesions to the ventromedial prefrontal cortex (vmPFC) and insula. In the current study, we assessed the neural basis of betting choices in healthy participants, using functional magnetic resonance imaging of the Roulette Betting Task. In half of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 93 publications
(128 reference statements)
5
36
1
Order By: Relevance
“…The BrainSight software allows a-posteriori normalizing of individual coordinates with respect to the Montreal Neurological Institute (MNI) brain atlas, by means of an iterative algorithm that searches for an optimal projection of an individual brain to the MNI template. Averaged normalized MNI coordinates were −56, −60, 31 (SD: 3, 4, 2) and 60, − 53, 31 (SD: 2, 4, 2) for the left and right AG respectively (Fig.1), in line with parietal activations reported in previous neuroimaging studies of decision-making (Berns et al, 2008;Mohr et al, 2010;Studer et al, 2012). Average normalized MNI coordinates for the left and right PMC were −22, −3, 71 (SD: 2, 2, 1) and 23, −3, 71 (SD: 2, 3, 2), respectively, similar to those used in previous TMS studies (Davare et al, 2010;Duque et al, 2012).…”
Section: Tms Parameters and Set-upsupporting
confidence: 76%
See 1 more Smart Citation
“…The BrainSight software allows a-posteriori normalizing of individual coordinates with respect to the Montreal Neurological Institute (MNI) brain atlas, by means of an iterative algorithm that searches for an optimal projection of an individual brain to the MNI template. Averaged normalized MNI coordinates were −56, −60, 31 (SD: 3, 4, 2) and 60, − 53, 31 (SD: 2, 4, 2) for the left and right AG respectively (Fig.1), in line with parietal activations reported in previous neuroimaging studies of decision-making (Berns et al, 2008;Mohr et al, 2010;Studer et al, 2012). Average normalized MNI coordinates for the left and right PMC were −22, −3, 71 (SD: 2, 2, 1) and 23, −3, 71 (SD: 2, 3, 2), respectively, similar to those used in previous TMS studies (Davare et al, 2010;Duque et al, 2012).…”
Section: Tms Parameters and Set-upsupporting
confidence: 76%
“…Previous neuroimaging studies found that the AG is activated during decision-making (Ernst et al, 2004;Labudda et al, 2008;Vickery and Jiang, 2009) and moreover, showed that hemodynamic responses in this area during the choice process reflect the probability Berns et al, 2008;Studer et al, 2012) and variance (Symmonds et al, 2011) of potential outcomes. The AG is also thought to be a key area for visuospatial attention.…”
Section: Introductionmentioning
confidence: 97%
“…Neuroimaging studies have reliably shown insula's involvement in experimental tasks addressing risk-taking, monetary rewards, and punishment (Critchley et al, 2001;Kuhnen and Knutson, 2005;Clark et al, 2008;Preuschoff et al, 2008;Studer et al, 2012). An abnormal top-down regulation of emotional processing in the insular cortex has been proposed to have a key role in the pathophysiology of depression (Sliz and Hayley, 2012), which is associated with a blunted emotional response to normally pleasant or rewarding stimuli (Snaith, 1993).…”
Section: Proportional Change In Insula Response To Positive Outcomes mentioning
confidence: 99%
“…27 Neuroimaging and lesion studies have consistently shown an involvement of the anterior insula in risk-taking during experimental tasks involving monetary reward and punishment. [28][29][30][31][32] Specifically, insula activity has been associated with risk-averse financial decisions, 29,31,33 and is suggested to be involved in learning the negative value of loss-predicting cues. 34 In good agreement with its functional involvement in risk-taking, in both the high-risk and the low-risk twins, the anterior insula scaled its activity during the choice phase to the risk of the gamble, along with other brain regions that were previously shown to be involved in risk-related decision making.…”
Section: Insula and Risk Takingmentioning
confidence: 99%